Time-Series Visualization: Highlighting Patterns and Deviations - Maçãs, Catarina Sofia Henriques (2021)
Doctoral thesis submitted in partial fulfilment of the Doctoral Program in Information Science and Technology supervised by Professor Fernando Jorge Penousal Martins Machado and presented to the Department of Informatics Engineering of the Faculty of Sciences and Technology of the University of Coimbra.